Influência de fatores de meio sobre pesos de animais da raça Canchim - Mascioli, Arthur Dos Santos [UNESP]; De Alencar, Maurício Mello; Barbosa, Pedro Franklin; De Sena Oliveira, Márcia Cristina; De Novaes, Antônio Pereira (My University, 1996)
The objective of this study was to evaluate the effects of some environmental factors on weights at birth (BW), weaning (WW), yearling (YW), 18- (EW), and 24-months of age (TW) of Canchim cattle raised in five different herds in the State of São Paulo, Brazil. The observations were analyzed by the least squares method, with models that included the fixed effects of herd, year and month of birth, sex of calf and age of cow at calving, and the random effects of sire within herd. All effects included in the models significantly affected all traits studied. The animals born between the months of May and September were the lightest ones at birth and the heaviest ones at weaning, while those born between August and December were the lightest ones at 12 and 24 months of age and the heaviest ones at 18 months of age. The males were always heavier than the females, and the seven to nine-year-old cows produced the heaviest calves from birth to 24 months of age. The estimated least squares means were 36 kg (BW), 201 kg (WW), 227 kg (YW), 290 kg (EW), and 353 kg (TW). The results suggest that these environmental factors should be considered when animals of the Canchim breed are compared for selection.
Influence of environmental factors on weights of Canchim cattle
Keywords: Beef cattle; Growth traits; Non-genetic factors